Sanksi Pidana Terhadap Pelaku Tindak Pidana Pemilihan Umum di Indonesia - Vandamme, Rio (Universitas Islam Indragiri, 2024)
This research discusses the criminal sanctions against perpetrators of criminal acts of general elections in Indonesia. The main issues in this study include what is meant by elections and election violations, what are the criminal sanctions for perpetrators of violations in general elections in Indonesia, what are examples of cases of election crimes that have occurred in Indonesia, and what are the efforts made by related parties in handling cases of election violations in Indonesia. This study concludes that what is meant by general election is a democratization process used in many countries around the world to elect government leaders and represent Indonesian citizens in a government institution. Election violations are actions that are contrary to or not in accordance with laws and regulations related to general elections, as for the sanctions for perpetrators of election violations, if the perpetrator commits a violation in the form of providing false information in the campaign finance report, he will be subject to sanctions in the form of a maximum imprisonment of 1 year and a maximum fine of Rp. 12 million, if the perpetrator provides false information in the campaign report or unclear information, he will be subject to sanctions in the form of imprisonment for a maximum of 2 years and a maximum fine of Rp. 24 million and if the perpetrator provides incorrect information in filling in the voter's personal data, he will be subject to sanctions in the form of imprisonment for a maximum of 1 year and a maximum fine of Rp. 12 million, an example of a case of criminal election violations that have occurred in Indonesia is the case of money politics violations that occurred in the 2019 elections where the suspect named David H. Rahardja, who is a candidate for the DKI Jakarta DPRD from the Perindo party, was sentenced to six months in prison and a fine of Rp. 5 million, because he was caught giving cooking oil to citizens during a campaign. The efforts made by related parties regarding cases of general election violations in Indonesia are by conducting supervision in the frame of prevention, conducting socialization and also understanding to the public of potential violations that must be anticipated, mapping and identifying general election violations before conducting election supervision and coordinating, supervising, guiding and monitoring and evaluating the implementation of elections.